Lecanora ramulicola (H. Magn.) Printzen & P. F. May new to the Iberian Peninsula - Pérez Ortega, Sergio; Printzen, Christian (Botanica Complutensis, 2007)
L. ramulicola is reported from the Iberian Peninsula for the first time. A brief description is provided as well as some data about its ecology and some remarks on closely related species.